The Impossible Jew : Identity and the Reconstruction of Jewish American Literary History - Schreier, Benjamin (Book collections on Project MUSE., 2015)
He destroys in order to create. In a sweeping critique of the field, Benjamin Schreier resituates Jewish Studies in order to make room for a critical study of identity and identification. Displacing the assumption that Jewish Studies is necessarily the study of Jews, this book aims to break down the walls of the academic ghetto in which the study of Jewish American literature often seems to be contained: alienated from fields like comparative ethnicity studies, American studies, and multicultural studies; suffering from the unwillingness of Jewish Studies to accept critical literary studies as.